Discovery of Pantoea stewartii ssp. stewartii genes important for survival in corn xylem through a Tn‐Seq analysis. (30th March 2018) - Duong, Duy An; Jensen, Roderick V.; Stevens, Ann M.
Summary: The bacterium Pantoea stewartii ssp. stewartii causes Stewart's wilt disease in corn. Pantoea stewartii is transmitted to plants via corn flea beetles, where it first colonizes the apoplast causing water‐soaked lesions, and then migrates to the xylem and forms a biofilm that blocks water transport. Bacterial quorum sensing ensures that the exopolysaccharide production necessary for biofilm formation occurs only at high cell density. A genomic‐level transposon sequencing (Tn‐Seq) analysis was performed to identify additional bacterial genes essential for survival in planta and to provide insights into the plant–microbe interactions occurring during wilt disease. A mariner transposon library of approximately 40 000 mutants was constructed and used to inoculate corn seedlings through a xylem infection model. Cultures of the library grown in Luria–Bertani (LB) broth served as the in vitro pre‐inoculation control. Tn‐Seq analysis showed that the number of transposon mutations was reduced by more than 10‐fold for 486 genes in planta compared with the library that grew in LB, suggesting that they are important for xylem survival. Interestingly, a small set of genes had a higher abundance of mutants in planta versus in vitro conditions, indicating enhanced strain fitness with loss of these genes inside the host. In planta competition assays retested the trends of the Tn‐Seq data for several genes, including two outer membrane proteins, Lon protease and two quorum sensing‐associated transcription factors, RcsA and LrhA. Virulence assays were performed to check for correlation between growth/colonization and pathogenicity. This study demonstrates the capacity of a Tn‐Seq approach to advance our understanding of P. stewartii –corn interactions.